Lateral intracerebroventricular injection of Apelin-13 inhibits apoptosis after cerebral ischemia/reperfusion injury - Yan, Xiao-ge (Neural Regen Res, 2015)
Apelin-13 inhibits neuronal apoptosis caused by hydrogen peroxide, yet apoptosis following cerebral ischemia-reperfusion injury has rarely been studied. In this study, Apelin-13 (0.1 μg/g) was injected into the lateral ventricle of middle cerebral artery occlusion model rats. TTC, TUNEL, and immunohistochemical staining showed that compared with the cerebral ischemia/reperfusion group, infarct volume and apoptotic cell number at the ischemic penumbra region were decreased in the Apelin-13 treatment group. Additionally, Apelin-13 treatment increased Bcl-2 immunoreactivity and decreased caspase-3 immunoreactivity. Our findings suggest that Apelin-13 is neuroprotective against cerebral ischemia/reperfusion injury through inhibition of neuronal apoptosis.